IMPLEMENTASI PRINSIP GOOD CORPORATE GOVERNANCE DALAM PERUSAHAAN TERBUKA - Redika Regina Cindy; Herman Setiawan; Zulfikri Toguan (STKIP Subang, 2026)
Good Corporate Governance (GCG) is a corporate management system grounded in the principles of transparency, accountability, responsibility, independence, and fairness as the foundation of healthy and sustainable governance in publicly listed companies. This normative study analyzes three key issues, namely the construction of GCG principles within the legal framework of publicly listed companies in Indonesia, the implementation mechanism of GCG in banking companies listed on the Indonesia Stock Exchange, and the legal implications of GCG implementation on firm value. The approach employed is a statutory approach and a conceptual approach by examining various regulations, legal doctrines, and relevant academic literature. The results indicate that Indonesia's GCG legal framework has developed significantly through various sectoral regulations, although implementation gaps remain a structural challenge requiring institutional strengthening and consistent law enforcement. Optimal application of GCG principles is proven to positively correlate with increased firm value through improved financial performance, risk management efficiency, and investor confidence. This study recommends cross-sectoral GCG regulatory harmonization as a strategic step in strengthening the governance of national publicly listed companies.